Independent Effects of Cardiorespiratory Fitness, Vigorous Physical Activity, and Body Mass Index on Clinical Gallbladder Disease Risk - Williams, Paul T. (2008)
BACKGROUND AND AIMS: Incident self-reported physician-diagnosed clinical gallbladder disease was compared to BMI, body dimensions, physical activity (km/day run) and cardiorespiratory fitness (10 km race speed, meters per second [m/s]) in 29,110 male and 11,953 female runners. METHODS: Physician-diagnosed gallbladder disease was reported by 166 men (0.57%) and 112 women (0.94%) during (mean ± SD) 7.74 ± 1.84 and 7.42 ± 2.10 years of follow-up, respectively. RESULTS: There was a progressive increase in age-adjusted risk with increasing BMI that accelerated sharply above 27.5 kg/m(2). Even among ostensibly healthy-weight women, the age-adjusted risk was significantly greater above 22.5 kg/m(2) vis-à-vis the leanest women (P = 0.04). Age-adjusted risk declined with increasing fitness in both sexes. Compared to the least fit men and women, men who ran faster than 4.75 m/s had 83% lower risk (75% lower when adjusted for km/day and BMI) and women who ran faster than 4 m/s had 93% lower risk (85% lower adjusted for km/day and BMI). The fittest men (≥4.75 m/s) were at significantly less risk than men who ran <3.25 m/s (P <0.003) and between 3.25 and 3.75 m/s (P = 0.03), and the fittest women (≥4 m/s) were at significantly less risk than those who ran <2.8 m/s (P < 0.0001), between 2.8 and 3.2 (P = 0.0004), 3.2 and 3.6 (P = 0.002), and 3.6 and 4.0 m/s (P = 0.005). Adjustment for BMI accounted for more of the risk reduction associated with fitness in women than men. The risk for clinical gallbladder disease was also significantly related to usual running distance (men: P = 0.01; females: P = 0.008), which was attributable to the leanness of the longer-distance runners. CONCLUSION: Clinical gallbladder disease risk was (a) concordantly related to BMI, (b) inversely related to usual running distance, and (c) inversely related to cardiorespiratory fitness independent of physical activity levels.